2021
DOI: 10.1111/icad.12508
|View full text |Cite
|
Sign up to set email alerts
|

Bat–bat fly interactions in Central Panama: host traits relate to modularity in a highly specialised network

Abstract: Recently, network approaches have gained increasing popularity in studies of species interactions. These analyses provide important information about structural and functional organisation, as well as on the dynamics of species interactions. Common model systems for network studies include seed dispersal, pollination, and also parasite interactions. Bat flies (Diptera: Streblidae, Nycteribiidae) are obligate blood‐sucking ectoparasites of bats. Resource partitioning allows multiple fly species to co‐occur on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 64 publications
2
16
1
1
Order By: Relevance
“…Interaction patterns at the local scale (Durán et al, 2019;Fagundes et al, 2017;Hiller et al, 2021) may hide variations in the relationship between species, but when observed at a larger scale may reveal modulations, as we detected here. Knowing that parasites are highly specific and that their distribution is limited not only by the presence of their hosts but also by other environmental variables (Marshall, 1982), the latitudinal variation in the structuring of the ecological networks was expected.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Interaction patterns at the local scale (Durán et al, 2019;Fagundes et al, 2017;Hiller et al, 2021) may hide variations in the relationship between species, but when observed at a larger scale may reveal modulations, as we detected here. Knowing that parasites are highly specific and that their distribution is limited not only by the presence of their hosts but also by other environmental variables (Marshall, 1982), the latitudinal variation in the structuring of the ecological networks was expected.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, the system is a model also because of the evolutionary characteristics of ectoparasites, particularly their high specificity — about 70% to 90% of bat flies in the Neotropic parasitize a specific species or genus of bat (Dick, 2007; Dick & Gettinger, 2005; Marshall, 1982) — adenotrophic viviparity, and the presence of winged, brachypterous, and wingless species (Marshall, 1982). Those diverse attributes found in the two groups contribute to different infestation patterns (Hiller et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…2018) and bat fly collection (Table 1) tend to be higher in the wet season, and the greater combined host species richness at this time enhances the probability of bat flies switching hosts within bat roosts (Dick 2007; Hiller et al. 2021). Although Zarazúa‐Carbajal et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the second half of the 2010s decade, the use of interaction networks contributed to an alternative way to study the bat and bat-ectoparasite ecological interactions helping to build a broader understanding to studies including eco-epidemiology, endosymbiosis, and hyperparasitism (Fagundes et al 2017 ; Sándor et al 2018 ; Jensen et al 2019 ). From 2020 onwards, new data are added to the description of interactions within caves and to the reports of viruses found in bat-flies and in bats (Bennett et al 2020 ; Hiller et al 2021 ; Tlapaya-Romero et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%